КОНЦЕПЦИЯ ВРОЖДЕННЫХ ЯЗЫКОВЫХ СПОСОБНОСТЕЙ В КОНТЕКСТЕ ИДЕЙ СОВРЕМЕННОЙ НАУЧНОЙ ФИЛОСОФИИ (Филолошке студије, 2019)
The author investigates the development of the concept "inherent knowledge" in history of philosophy. The multivalence of this concept is determined by a history, semantics, and concrete position of the philosopher. The author puts the problem in context of modern form of philosophy – the conception of single naturally determined world development.